Avaliação de fatores prognósticos de fertilidade em mulheres com endometriose intestinal submetidas à tratamento cirúrgico conservador - Leci Veiga Caetano Amorim (2018)
Introduction: Deep infiltrative endometriosis (DIE) alters fertility and quality of life. The monthly fertility rate can occur reduction up to 50% in the presence of the disease. However, the reason for the impact on fertility is unclear. It affects 20-35% of women with endometriosis and intestinal involvement can occur in 6% to 12%. The main problem in patients with colorectal endometriosis is to determine the best therapeutic strategy according to the priority of the patient. When it is improving symptoms and quality of life, several studies emphasize the positive impact of surgery, but when the patient's priority is to conceive, there is no consensus whether surgery or assisted reproductive techniques are best indicated as first line. Objective: Try to identify some perioperative data: signs and symptoms, ultrasound findings and magnetic resonance imaging, staging, extension, location of lesions that correlate with the probability of future pregnancy in women with intestinal endometriosis undergoing surgical treatment. Patients and methods: This was a retrospective study carried out at the Biocor Hospital with patients undergoing videolaparoscopy because of DIE from May 2007 to May 2016. A total of 212 surgeries were performed during this period, 106 of which were DIE with intestinal involvement. Of these, 60 patients attempted to become pregnant after surgery. The outcome analyzed was the pregnancy rate. In addition, the prognostic factors evaluated were signs and symptoms, findings of imaging, staging, extension, location of lesions, previous pregnancy history. This study was approved by the local ethics committee. Statistical analysis was performed in SPSS version 18 software. The level of significance was 0.05. Results: Of the 60 patients who wished to conceive, 28 (46.7%) became pregnant, 19 spontaneously and 9 by IVF. The mean age and time of infertility prior to surgery were lower in the group of patients who became pregnant compared to those who did not. The mean interval between surgery and pregnancy was 8.1 months overall, being lower in patients who became pregnant spontaneously than those who underwent IVF (6 and 12 months respectively). In association with intestinal lesion, other sites were involved, such as uterine ligaments (100%), endometrioma (68.3%) and bladder (21.7%). Severe endometriosis was found in 93.3% of patients, intestinal symptoms prior to surgery were present in all patients and only 8 (13%) recurred after surgery. The main findings of this study are that age and time elapsed between surgery and pregnancy are important predictors. Conclusion: In summary, the Brazilian women studied here with a diagnosis of deep endometriosis associated with intestinal involvement, submitted to surgical treatment by a multidisciplinary team and who, after designing, presented as relevant prognostic factors the age and the time elapsed between surgery and pregnancy. Women younger than 35 are more likely to become pregnant spontaneously up to 6 months after surgery. Association with endometrioma, urinary tract injury or scoring in the revised American Society for Reproductive Medicine classification of the disease did not appear to exert negative influence on the results